Technology enhanced learning in higher education: results from the design of a quality evaluation framework - Casanova, Diogo (2021)
This paper presents an ongoing research that deals with the development of a quality framework of reference for Technology Enhanced Learning in Higher Education. We will present the design of the methodology used for building our framework linked to a collection of internal and external references. We will also present criteria derived from this data collection phase. We will set landmarks for discussing what determines quality in Technology Enhanced Learning and what dimensions must be considered to evaluate its quality.